A child with Li–Fraumeni syndrome: Modes to inactivate the second allele of TP53 in three different malignancies. Issue 8 (18th March 2015) - Schlegelberger, Brigitte; Kreipe, Hans; Lehmann, Ulrich; Steinemann, Doris; Ripperger, Tim; Göhring, Gudrun; Thomay, Kathrin; Rump, Andreas; Di Donato, Nataliya; Suttorp, Meinolf
Abstract : Here we report on a child with Li–Fraumeni syndrome with a de novo TP53 mutation c.818G> A, who developed three malignancies at the age of 4 months, 4 and 5 years, respectively. We show that (i) in the choroid plexus carcinoma, the germline mutation was detected in a homozygous state due to copy‐neutral LOH/uniparental disomy, (ii) in the secondary AML, a complex karyotype led to loss of the wild‐type TP53 allele, (iii) in the Wilms tumor, the somatic mutation c.814G> A led to compound heterozygosity. The findings show that the complete inactivation of TP53 by different mechanisms is an important step towards tumorigenesis. Pediatr Blood Cancer 2015;62:1481–1484. © 2015 Wiley Periodicals, Inc.